Kesulitan Keuangan, Proporsi Hutang dan Peluang Investasi, Audit Delay: Peran Moderasi Dewan Komisaris Independen - Reni Suhendi; Amrie Firmansyah (Owner : Riset dan Jurnal Akuntansi, 2022)
The accuracy of delivering information will be meaningful if presented on time because it benefits decision-making for its users. The delay in submitting financial statements causes erratic stock movements because investors assume that the company is experiencing problems. This study examines the effect of financial distress, debt proportion and investment opportunity set on audit delay moderated by an independent board of commissioners. This study uses secondary data sourced from www.idx.co.id. The data used consists of information on financial statements that have been audited and listed on the IDX from 2017 to 2020. The sample used in this study amounted to 440 observations based on purposive sampling. This study concludes that financial distress and debt proportion can prolong audit delays in companies. At the same time, the investment opportunity set can reduce audit delays. This study proves that the existence of independent commissioners in the company cannot supervise the company's financial condition and use of debt, which causes the audit delay to be longer. In addition, the independent board of commissioners is also unable to dominate the policies taken on planning in the company's investment activities. This research suggests that OJK needs to review the deadline for submitting financial reports related to the supervision of companies listed on the IDX and the protection of investors in the Indonesian capital market. Keywords: financial distress; debt proportion; investment opportunity set